Psychotic Episode following Treatment with Hydroxychloroquine in a 17- Year-Old Female Adolescent with Cutaneous Lupus Erythematosus: A Drug Causality Supported by a Literature Review and a Worldwide Pharmacovigilance Database Search - Cravero, Cora; Hie, Miguel; Barete, Stéphane; Spiers, Solène; Brunelle, Julie; Lebrun-Vignes, Bénédicte; Cohen, David (Archives of Clinical and Medical Case Reports, 2021)
Background: Hydroxychloroquine (HCQ), a useful treatment for chronic dermatologic or rheumatologic diseases, has recently gathered widespread attention as a possible treatment for COVID-19 infection. However, its rare et severe neuropsychiatric side effects (NSE), such as psychosis and suicidal tendencies, are poorly documented, especially in youths. Case presentation: We present the first case on a 17-yearold girl of severe acute psychosis with a suicide attempt during HCQ treatment in association with thalidomide for chronic and refractory discoid lupus erythematosus. Drug causality was evaluated using the updated French causality assessment method. We performed a literature review and a worldwide pharmacovigilance database search on psychotic features after HCQ and thalidomide treatment. We found six cases in the literature and 53 cases (psychotic disorder: N=45, 3.7% and acute psychosis: N=8, 0.7%) in the pharmacovigilance database reporting the occurrence of psychotic symptoms under HCQ and none under thalidomide. The intrinsic and extrinsic imputability scores support the hypothesis that HCQ induced psychosis and suicide attempt in our patient. Withdrawing HCQ resulted in a dramatically improved situation, which remained perfectly stable after 3 years of follow-up. Conclusion: In HCQ-induced psychosis, recovery may be obtained with HCQ withdrawal, no future HCQ reintroduction, and, for the most serious manifestations, a short period of antipsychotic medication. Clinicians need to be aware of the NSE of HCQ and the appropriate interventions to be carried out.